Analisis Pembiayaan Musyarakah dan Murabahah Terhadap Kredit Macet Pada Koperasi Simpan Pinjam dan Pembiayaan Syariah Baitul Maal Wat Tamwil Bina Usaha Mandiri Indonesia - Utary Widiatiningrum; Rakhmat; Safrudin (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
One of the functions of Islamic financial institutions is to collect public funds which are then channeled back to them through a community financing mechanism. At KSPPS BMT Bina Usaha Mandiri Indonesia there is musyarakah and murabahah financing. This study aims to determine musyarakah financing or murabahah financing which is more at risk of bad loans and to find out the settlement of bad loans at KSPPS BMT Bina Usaha Mandiri. This research is descriptive in nature with primary data collected through interviews, observation, and supported by literature study. Data analysis used qualitative data analysis techniques, which consisted of data simplification, presentation and conclusion. The results of the analysis from this research show that bad credit in musyarakah financing can reduce bad credit more, seen from data in 2020, bad credit which occurred with a percentage of 1.79% decreased by 0.27% to 1.52% and at the end of 2021 and continues to decline in 2022 by 0.51% to 1.52%. If you look at the nominal value, bad credit has increased but the percentage has decreased, this is because the financing disbursed has also increased and bad credit in musyarakah financing is more risky, where musyarakah financing experiences higher bad credit in 2020 and 2022, that musyarakah financing with a greater percentage of bad credit in 2022 amounting to 1.01% while murabahah financing is only 0.55% and in 2020 bad credit financing for musyarakah financing is 1.79% worth IDR 14,619,037 while 1.01% murabahah financing. However, in 2021, the percentage of bad debts in murabahah financing is greater, namely 2.30% worth IDR 5,086,628 while musyarakah financing is 1.52% but if the percentage of bad loans is totaled over 3 years then the value of musyarakah financing is more large, namely 4.32% compared to murabahah 3.86%. Then the resolution of bad debts carried out by KSPPS BMT Bina Usaha Mandiri Indonesia is by directly writing off the financing using the direct write off method, namely directly writing off the financing to the receivables account which immediately reduces the total receivables on the balance sheet and is immediately charged to profit and loss on the PPAP Opex expense account.